COMMON PATHOGENS ASSOCIATED WITH ENDOCARDITIS IN HAZARA DIVISION - Wazir, Mehr Dil Khan; Alam, Malik Mahmood; Khan, Niaz Ali (Journal of Ayub Medical College Abbottabad, 1996)
Fifty-one cases of suspected infective endocarditis were studied in detail in Paediatrics Department of Women and Children Hospital, Abbottabad. Underlying heart disease was congenital in six patients and possible rheumatic in forty-five patients. Cultures were negative in thirty-nine patients and positive in twelve patients with Streptococcus viridans in five patients and Staphylococcus aureus in seven patients. Most of the patients responded to Penicillin and Streptomycin except a few with Staphylococcal aetiology who responded well to a combination of either Ampiclox and Gentamicin or Cephradin (Velosef) and Gentamicin.